Identifying barriers and enablers to patient-centred care using drama in the context of HIV/AIDS: The case study of Ndlovu care group Elandsdoorn clinic - Nkosi, Lesley Vusi (My University, 2014)
This empirical study, based on two years of research, attempts to explore the efficacy of patient-centred care in a rural context. Drawing on an integrated research approach, employing ethnography, participatory action research, applied drama, community capacity enhancement and patient-centred care, this work aims to implement a theatre-based intervention at a site in order to elicit dialogue with health care practitioners delivering a service at a community based HIV/Aids and TB clinic. It explores the attitudes and experiences of five health care practitioners in relation to their working context, encouraging a critical reflexive praxis in the clinic. This explanatory study examines facilitators and the barriers affecting patient-centred care in a semi-rural context around the major themes of ‘Time’, ‘Systems’ and the ‘Human Factor’ and how these connect with compassion and affect patient-centred care. This study, of a clinic, which focuses on health care around HIV/Aids and TB in Elandsdoorn, Limpopo, will demonstrate that drama as a tool for dialogue can assist health practitioners to explore their own attitudes and experiences through reflection. The hope is that the realisation of what can be learnt through dialogue will elicit in others a desire to change and to explore the basis of patient-centred care and its underlying sense of compassion. This study, compiled by a person receiving antiretroviral treatment, employs qualitative methods and draws on an insider perspective through an ethnographic approach.